The Effect of Value Perception, Product Quality, and Product Trust on the Purchase Intention of Cushion Glad 2 Glow Die-Commerce Tiktok Shop Products (Case Study Among Generation Z Surakarta) - Lilik Intan Sari; Sri Wijiastuti; Achmad Choerudin (ProBisnis : Jurnal Manajemen, 2026)
This study aims to investigate how Perception of Value, Product Quality, and Product Trust affect the Purchase Intention of Cushion Glad 2 Glow on  the TikTok Shop E-Commerce platform  which is the focus of this study. The approach used in this study is quantitative. Data was collected through a questionnaire distributed to 80 respondents from Generation Z in Surakarta, with a sampling technique using Google Form. Data analysis was carried out with the help of SPSS version 21. The results show that Value Perception has a positive and significant influence on Purchase Intent, while Product Quality has a negative and insignificant influence, and Product Confidence shows a positive but not significant influence on Purchase Intent.